Features of development in the implementation of investment projects for the construction of objects of different functional purposes. - Kishchenko, T.; Gusarova, L. (Ways to Improve Construction Efficiency, 2018)
The article considers the individual character of the development of investment projects implemented by construction companies in the construction market. The role of individual factors is determined, the significance of which varies depending on the functional purpose of the construction objects. The specificity of functions of development companies in the process of realizing housing construction projects, trade and office facilities is analyzed.